2016
DOI: 10.1115/1.4033989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of System Evolvability Based on Usable Excess

Abstract: Complex, large-scale engineered systems are an integral part of modern society. The cost of these systems is often high, while their ability to react to emergent requirements can be low. This paper proposes evolvability, based on usable excess, as a possible metric to promote system longevity. An equation for the usability of excess, previously defined only in terms of quantity, is improved to include the attributes of type, location, and form as well as quantity. A methodology for evaluating a system's evolva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…length, area, and volume (space) and structural strength. Several authors have quantified excess (see for example [23], [24]) and shown that it is fungible (i.e. different types could be traded off with each other) [16].…”
Section: Redundancymentioning
confidence: 99%
“…length, area, and volume (space) and structural strength. Several authors have quantified excess (see for example [23], [24]) and shown that it is fungible (i.e. different types could be traded off with each other) [16].…”
Section: Redundancymentioning
confidence: 99%
“…This type of system attribute has been labeled "excess", and research has begun to explore what excess is and what it's properties are [13][14][15][16]. In this paper excess is defined as a modified version of that found in Allen [16] and Tackett [15] to be the quantity of usable surplus of a system resource that is likely to be prohibitively expensive to increase with inservice design changes. A prohibitive cost would be one for which the system decision maker would prefer performance degradation or retirement to configuration change.…”
Section: Introductionmentioning
confidence: 99%
“…This line of inquiry is important to CES design because it addresses one of the aspects of system design that may limit its lifetime. One example cited in literature is that of a nuclear powered aircraft carrier [16]. The electrical power generated by the carrier is a limiting factor for the addition or modification of systems.…”
Section: Introductionmentioning
confidence: 99%